2020
DOI: 10.1108/caer-04-2020-0055
|View full text |Cite
|
Sign up to set email alerts
|

The impact of epidemics on agricultural production and forecast of COVID-19

Abstract: PurposeThis article investigates the mechanism of the direct and indirect effects of epidemics on agricultural production and projects the impact of COVID-19 on agricultural output in China.Design/methodology/approachThis article first adopts a dynamic panel model and spatial Durbin model to estimate the direct and indirect effects, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 39 publications
(40 reference statements)
0
51
0
3
Order By: Relevance
“…Many agricultural industries around the world have witnessed serious impacts of the COVID-19 pandemic, including two Asian major economies, China and India [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. The countries affected by COVID-19 were compelled to rethink and amend their food and agriculture strategies in order to ensure that public food sources remained sufficient and accessible.…”
Section: Discussionmentioning
confidence: 99%
“…Many agricultural industries around the world have witnessed serious impacts of the COVID-19 pandemic, including two Asian major economies, China and India [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. The countries affected by COVID-19 were compelled to rethink and amend their food and agriculture strategies in order to ensure that public food sources remained sufficient and accessible.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 has impacted the global economy significantly including India. Few of the recent researches have tried to analyze the implications of COVID-19 pandemics on agricultural productions and supply chain globally (Pu & Zhong, 2020;Kumar, Padhee, & Kumar, 2020;Gillespie, 2020;Galanakis, 2020;Singh & Neog, 2020;Solomon, Pratap, & Swapna, 2020;Weersink, von Massow, & McDougall, 2020;Sharma, Talan, & Jain, 2020;Zhang et al, 2020). Pu and Zhong (2020) argued that unreasonable restrictions would block the outflow channels of agricultural products, hinder necessary production inputs, destroy production cycles, and finally undermine production capacity and suggested that there is a need to ensure effective logistics for agricultural products, ensure effective supply of critical inputs, provide various supports to agricultural production and farmers and make use of innovative methods to promote sales such as e-tailing.…”
Section: Introductionmentioning
confidence: 99%
“…As a means to document the existing situation in the agricultural sector, predicting the potential effects of the COVID-19 pandemic and suggesting measures to mitigate them, several studies have been conducted. Some of them analyzed solely the impact of the virus on agricultural production regarding the first infected by COVID-19 countries, namely China [18,19] and later Italy [7,[20][21][22]. In contrast, some studies dealt with the agricultural sector of countries, which were later infected by the viral pandemic, including countries from the rest of Asia (India [23,24] and Iran [25]), Oceania (Australia [26] and New Zealand [27]), Europe (rest of EU [5,28] and the United Kingdom (UK) [29]) as well as America (Argentine [30], Peru [31], Canada [32][33][34][35][36] and the US [14,37,38]).…”
Section: Pandemic Effects On Agriculutral Sectormentioning
confidence: 99%